PENGARUH PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN EMAS 22% DI KOTA KRAKSAAN KABUPATEN PROBOLINGGO (Studi Pada Toko Pusaka Mas) - Ibnu Hajar Dewantara (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to analyze the influence of perceived value on purchasing decisions gold 22% Kraksaan city probolinggo. To find out how much influence the dependent variable (buying decisions) to the independent variables (Quality/Performance Value, Emotional Value, Functional Value, Social Value). This study uses multiple regression analysis with SPSS version 17.0. This data collection method uses a questionnaire to  consumer of  Pusaka Mas  store  in Kraksaan..  Questionnaires were distributed  100 questionnaires. The results of studies using multiple linear regression analysis, showed that simultaneous variabel  quality/performance value  (X1), emotional value  (X2), functional value  (X3), social value  (X4),  has a significant influence on buying decisions (Y). While partial, variable funtcional value showed a significant effect on decision buying consumen. Keywords: Perceived Value, Quality/Performance Value, Emotional Value, Functional Value, Social Value, and Purchase Decision.